Jazyčestvo i Drevnjaja Rus'. St.-Petersburg 1914 - Anickov, Evgenij V. (Specimina philologiae Slavicae, 1995)
With the reprint of E.V. Aničkov's "Jazyčestvo i Drevnjaja Rus'" makes a standard work accessible in general, approaching pre-Christian Russia from a very special perspective: on the one hand, it deals with the Christianization and thus the suppression of pagan culture, but on the other hand with the survival of the same Culture in the monuments of Christian times. In Cyrillic, Literaturverz. Pp. 16-25, former ed. Also as: Zapiski Istoriko-filologičeskago fakul'teta Imperatorkago S.-Peterburgskago Universiteta.